Integrating Palembang’s Local Wisdom into a STEM-Based e-Module on Particle Dynamics to Foster Students’ Creative Thinking Skills - Pratiwi, Sri Mindia Vanessa; Wiyono, Ketang; Ismet, Ismet (Jurnal Pendidikan MIPA, 2025)
This research aims to produce STEM-based particle motion dynamics e-modules in the context of local wisdom to train students' creative thinking skills. This research uses the 4D development model, namely the defining, planning, developing, and disseminating stages. This research involved 9 experts and 10 students in the limited trial stage and 20 students in the wider trial stage. The effectiveness test in this study involved 46 students of class XI from SMAN 2 Palembang. Creative thinking skills were measured using a creative thinking skills test which was then analyzed using the normalized N-Gain formula. The results of the expert appraisal validation showed that the content aspect scored 81% with very valid criteria, the media design aspect scored 74%, and the language aspect reached 76%, both of which were declared valid. At the broad trial stage, all aspects showed very practical results, with details of the ease of use aspect obtaining a percentage of 98%, the appearance and design aspects reached 95%, and the material presentation and benefit aspects each obtained a percentage of 96%. The effectiveness test showed that the average pretest and posttest scores were 27.96 and 79.45, with an overall N-Gain value of the creative thinking skills indicator of 0.7, which is in the high category. The results of this study conclude that the STEM-based particle motion dynamics e-module in the context of Palembang local wisdom has been successfully developed and proven to have good validity, practicality, and effectiveness in training students' creative thinking skills, so it is feasible to use in physics learning in high schools.       Keywords: e-modules, physics, STEM, local wisdom, validity, practicality.